2015
DOI: 10.1167/15.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Does attention speed up processing? Decreases and increases of processing rates in visual prior entry

Abstract: Selective visual attention improves performance in many tasks. Among others, it leads to "prior entry"--earlier perception of an attended compared to an unattended stimulus. Whether this phenomenon is purely based on an increase of the processing rate of the attended stimulus or if a decrease in the processing rate of the unattended stimulus also contributes to the effect is, up to now, unanswered. Here we describe a novel approach to this question based on Bundesen's Theory of Visual Attention, which we use t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 69 publications
2
48
0
Order By: Relevance
“…These findings confirm that in conditions of maximal uncertainty, attended stimuli are consistently reported as being perceived before unattended ones, in accordance with the concept of prior entry (Schettino et al, 2016;Shore et al, 2001;Spence & Parise, 2010;Titchener, 1908;Tünnermann et al, 2015;Tünnermann & Scharlau, 2016). …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings confirm that in conditions of maximal uncertainty, attended stimuli are consistently reported as being perceived before unattended ones, in accordance with the concept of prior entry (Schettino et al, 2016;Shore et al, 2001;Spence & Parise, 2010;Titchener, 1908;Tünnermann et al, 2015;Tünnermann & Scharlau, 2016). …”
Section: Discussionsupporting
confidence: 86%
“…Importantly, several studies have shown that, when these non-attentional confounds are minimized and carefully controlled, prior entry is still a robust attentional effect (Schettino et al, 2013(Schettino et al, , 2016Spence & Parise, 2010;Tünnermann, Petersen, & Scharlau, 2015;Tünnermann & Scharlau, 2016).…”
Section: Measuring the Prior Entry Effectmentioning
confidence: 99%
“…The letter stimuli were made of little squares on a 5×7 grid that extended 0.8 × 1.3 • of visual angle. Targets of this font have been used in several previous experiments [16,17]. Examples are presented in Figure 2.…”
Section: Stimulimentioning
confidence: 99%
“…Its cause thus lies before or at the beginning of stimulus encoding, leaving the decision mechanism perfectly deterministic. This model is an extension of our earlier work [15][16][17][18][19][20][21], in which we derived a TOJ model from Bundesen's [22,23] theory of visual attention (TVA). Notably, TVA has been successfully applied in many domains of attention research and different experimental paradigms (e.g., whole report, partial report, and attentional dwell time experiments).…”
Section: Introductionmentioning
confidence: 99%
“…Originally demonstrated by Raymond, Shapiro, and Arnell (1992), the AB refers to an impairment in identification accuracy for the second of two 1 There is an interesting and enduring discussion as to whether or to what extent prior entry reflects judgment biases or reflects the influence of attention on processing rate (Jaskowski, 1993;) and also whether any changes in processing rate involve the attended or the unattended item (Tünnermann, Petersen & Scharlau 2015;Weiss, Hilkenmeier & Scharlau 2013). The assumption is made in the present work that prior entry speeds up the processing of the attended item.…”
mentioning
confidence: 99%